Development of Transcultural Multimedia Teaching Materials for BIPA Learners Based on Interpretative, Interpersonal, and Presentational Communication Models - Hani Herawati; Ade Hikmat; Herri Mulyono (LP. Ma'arif Janggan Magetan, 2025)
This study aims to develop transcultural multimedia teaching materials for learners of Indonesian as a Foreign Language (BIPA) using a three-mode communication approach: interpretive, interpersonal, and presentational. Employing a Research and Development (R&D) method, the process involved six key stages including needs analysis, planning, product development, and limited trials. Validation from five experts yielded an average score of 4.55, indicating high quality. A field trial involving 30 foreign learners demonstrated significant improvement in learner motivation, cultural understanding, and communication skills. This study's mixed-methods analysis demonstrates that a technologically advanced, culturally aware curriculum greatly improves students' language proficiency and critical intercultural competency, which are required for effective communication in the real world. Interactive features, contextual videos, and reflective activities effectively enhanced pragmatic competence and intercultural awareness. Participant feedback highlighted the need for more regionally diverse content and adaptive learning paths. This study underscores the importance of integrating cultural and technological elements in language education to foster comprehensive communicative and intercultural competence. In the end, these study findings offer a revolutionary BIPA model.